2013
DOI: 10.2174/15734064113099900002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Neoplastic Activity of 1,3-Diaza-2-Functionalized-Adamantan-6-One Compounds Against Melanoma Cells

Abstract: Four series of 1,3-diaza-2-functionalized-adamantan-6-one derivatives, bearing at the 2 position SO, SO₂, POCl and PO₂H functional groups, were synthesized via a key quadruple Mannich reaction, followed by transformation of an aminal functionality into the final 2-thia- and 2-phospha compounds. The compounds were tested for cytotoxic activity against the mouse B16-F10 melanoma cell line. Malignant melanoma is notorious for its high resistance to chemotherapy, and new anti-melanoma drugs are urgently needed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The synthesis and study of the antitumor activity of several series of 2-thio- and 2-phospho-containing 1,3-diazaadamantanes ( Fig. 13 ) against mouse melanoma cells B16-F10 were carried out by Sharabi-Ronen et al [ 49 ]. According to the authors, 2-thio-containing 1,3-diazaadamantanes ( 124 ) and ( 125 ) showed low activity against tumor cells (IC 50 > 200 µM).…”
Section: Biological Activity Of Azaadamantanesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis and study of the antitumor activity of several series of 2-thio- and 2-phospho-containing 1,3-diazaadamantanes ( Fig. 13 ) against mouse melanoma cells B16-F10 were carried out by Sharabi-Ronen et al [ 49 ]. According to the authors, 2-thio-containing 1,3-diazaadamantanes ( 124 ) and ( 125 ) showed low activity against tumor cells (IC 50 > 200 µM).…”
Section: Biological Activity Of Azaadamantanesmentioning
confidence: 99%
“…According to the authors, 2-thio-containing 1,3-diazaadamantanes ( 124 ) and ( 125 ) showed low activity against tumor cells (IC 50 > 200 µM). More promising results were obtained for phosphorus-containing analogs ( 126 ) and ( 127 ), which showed significant antitumor activity (IC 50 = 10–60 µM) [ 49 ]. In addition to the cytotoxicity of the resulting compounds, the authors studied the influence of the most active 5,7-di(4-(trifluoromethyl)benzyl-1,3-diaza-2-phosphoadamantanes ( 126 ) and ( 127 ) on the cell cycle and the activation of apoptosis.…”
Section: Biological Activity Of Azaadamantanesmentioning
confidence: 99%
“…Among these derivatives, 1,3-Diaza-adamantane derivatives have attracted great attention due to their interesting properties [9] such as antibacterial, and psychotropic activity [10][11]. Sharabi-Ronen et al have reported the anti-neoplastic activity of 1,3-Diaza-2-functionalized-adamantan-6-one compounds against melanoma cells [12]. They showed that the ability of the reported compounds to introduce apoptosis in melanoma cells was significant.…”
Section: ■ Introductionmentioning
confidence: 99%